Last men out : the true story of America's heroic final hours in Vietnam - Drury, Bob (Free Press, 2011)
"Last Men Out" tells the riveting story of the last 11 United States soldiers to escape South Vietnam on April, 30, 1975, the day America ended its combat presence.